The Role Of Time Planning And Time Organizing In Improving The Performance Of Employees (Field Study In The Faculty Of Literature And Humanities In Tishreen University) - Ghadeer, Bassem Ghadeer; Issa, Jameel; Othman, Haneen Nawwaf (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This study aimed to identify the role of time planning and time organizing in improving the personnel performance in the Faculty of Literature and Humanities at Tishreen University by defining the relationship between variables (time planning, time organizing) on one hand, and between employee performance variable on the other hand. The researcher depended on the deductive approach as a general approach for research and on the descriptive and analytical approach. She depended on simple random sampling and conducted a reconnaissance study, personal interviews and literary review. She also conducted a field study and organized, based on the literary review, two questionnaires distributing the first to a sample of administrative personnel and the second to a sample of students from the same research community, i.e. Faculty of Literature and Humanities at Tishreen University. SPSS was used to download and analyze available data. This study concluded to a set of results, the most important of which is the presence of a statistically significant effect of time planning and time organizing on improving personnel performance in the community under study, in addition to low personnel’s application of time planning and time organizing. هدفت الدراسة إلى التعرف على دور تخطيط وتنظيم الوقت في تحسين أداء العاملين في كلية الآداب والعلوم الإنسانية في جامعة تشرين من خلال تحديد العلاقة بين تخطيط وتنظيم الوقت وبين تحسين أداء العاملين، حيث اعتمدت الباحثة على المقاربة الإستنباطية كمنهج عام للبحث وعلى المنهج الوصفي والتحليلي، فاعتمدت على المعاينة البسيطة العشوائية وقامت بدراسة استطلاعية ومقابلات شخصية ومراجعة أدبية ثم قامت بإجراء دراسة ميدانية، ونظمت بناءً على المراجعة الأدبية استبانتان، قامت بتوزيع الأولى على عينة من العاملين الإداريين في كلية الآداب والعلوم الإنسانية، وقامت بتوزيع الثانية على عينة من الطلاب من مجتمع البحث نفسه. وتم الإعتماد على برنامجSPSS إصدار 25 لتفريغ وتحليل البيانات المتوفرة. وخلصت الدراسة إلى مجموعة من النتائج أهمها: وجود تأثير ذو دلالة إحصائية لتخطيط وتنظيم الوقت على تحسين أداء العاملين في المجتمع محل الدراسة، بالإضافة إلى انخفاض مستوى تطبيق العاملين لتخطيط وتنظيم الوقت.